2020
DOI: 10.1177/0093854820964834
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis and Criminal Offending: A Population-Based Data-Linkage Study

Abstract: This population-based case-control study examines the association between psychosis and criminal convictions in New South Wales (NSW), Australia, using data from several health and offending administrative data collections. Cases were individuals diagnosed with psychosis between 2001 and 2012 ( n = 86,461). For each case, two age- and sex-matched controls with no diagnosis of psychosis were selected. Criminal convictions were identified using the NSW Reoffending Database. Cases were approximately 5 times more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…In 2019–2020, nearly 55% of those released from Australian prisons in the past 2 years returned to corrective settings (Australian Government Productivity Commission, 2021). People with mental illness, including those diagnosed with psychosis, are at high risk of offending and return to the criminal justice system (Butler et al, 2006; Chowdhury et al, 2020; Douglas et al, 2009; Fazel and Grann, 2006; Fazel and Yu, 2011; Nielssen et al, 2019; Steadman et al, 2009). A meta-analysis of 204 studies found that psychosis was associated with a 49% to 68% increase in the odds of violence (Douglas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019–2020, nearly 55% of those released from Australian prisons in the past 2 years returned to corrective settings (Australian Government Productivity Commission, 2021). People with mental illness, including those diagnosed with psychosis, are at high risk of offending and return to the criminal justice system (Butler et al, 2006; Chowdhury et al, 2020; Douglas et al, 2009; Fazel and Grann, 2006; Fazel and Yu, 2011; Nielssen et al, 2019; Steadman et al, 2009). A meta-analysis of 204 studies found that psychosis was associated with a 49% to 68% increase in the odds of violence (Douglas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A study in NSW found a lower risk of recidivism in forensic patients who were found not guilty for reason of mental illness and received supervision and treatment (Hayes et al, 2014). Using a whole of population data-linkage study in NSW, we recently showed that the risk of offending was five times greater in the cohort of all individuals diagnosed with psychosis between 2001 and 2012 than a matched comparison group with no such diagnosis (Chowdhury et al, 2020). We examined the effectiveness of the NSW court diversion scheme and found that those with psychosis who received a court order for mental health treatment had a 12% reduction in the risk of reoffending than those who received a punitive sanction (Albalawi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for the high prevalence of mental illness in prisons is complex. Mental illnesses across the diagnostic spectrum have been found to be associated with both violent and non-violent offending (Chowdhury et al, 2021; Stevens et al, 2015), and particular symptoms, such as paranoia and delusional beliefs, have been shown to be important in driving some offending behaviour (Coid et al, 2013, 2016). As well as having a direct impact on the likelihood of offending, mental illness is associated with a number of factors that may increase the risk of criminal justice contact such as substance use (Kopak, 2021) and socio-economic indicators such as homelessness, unemployment and financial hardship, suggesting a process of the ‘criminalisation’ of the socially disadvantaged (Baldry and Russell, 2017).…”
mentioning
confidence: 99%
“…Individuals in prison with mental illness are a highly vulnerable group who experience higher levels of disadvantage and ill-health prior to incarceration and more adverse social and health outcomes post-release than those without (Cutcher et al, 2014).Accounting for the high prevalence of mental illness in prisons is complex. Mental illnesses across the diagnostic spectrum have been found to be associated with both violent and non-violent offending (Chowdhury et al, 2021;Stevens et al, 2015), and particular symptoms, such as paranoia and…”
mentioning
confidence: 99%
See 1 more Smart Citation